On the issue of waterway aeration (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article outlines the influence of the distance between weirs and specific water flow on the aeration capacity of weirs
Keywords: aeration, oxygen regime, assimilating capacity of water, aerated flow, aeration capacity of spillways